Peran Kepemimpinan Kepala Sekolah dalam Pengembangan Kompetensi Pedagogik Berbasis Digital - Gianluigi Maulana Dhielfitri; Yohamintin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the role of school principal leadership in developing teachers' digital-based pedagogical competence at SDIT Mentari 2. The research uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. The findings reveal that the principal plays a strategic role through four managerial functions: planning, organizing, implementing, and supervising. The principal designs digital training programs, forms a digital movement team, facilitates training and mentoring, and conducts continuous evaluation of teachers’ digital teaching practices. The implementation of the program is carried out in stages and involves active teacher participation, supported by adequate infrastructure and facilities. The study concludes that a transformative and participative leadership style is key to enhancing digital-based pedagogical competence. This leadership model can serve as a best practice reference for other schools in addressing the challenges of education in the digital era.